Anglo-Saxons, Anglo-Normands, Anglo-Français, Anglo-Celtiques - Pierre Flatrès (La Bretagne Linguistique, 1990)
The origin of the research whose preliminary results will be presented here is the observation that many of the names used on both sides of the Channel by historians, geographers and others to designate the peoples or human groups who live or have lived in the British Isles are inadequate to the terms or expressions used at the times concerned by the people concerned or by their neighbours, friends or enemies.